Performance Evaluation of Turkish Sustainability Funds via Fuzzy MCDM Approach - SUYADAL, Mehmetcan; GÜL, Yavuz; KARAMAŞA, Çağlar; PALA, Osman (International Journal of Contemporary Economics and Administrative Sciences, 2025)
In this research, we attempt to analyze the performance of 30 sustainability – themed funds traded in Turkey via IVCIF AHP – ERUNS method. We also employ sensitivity and comparison analyses and the dataset spans August 16, 2022 to October 09, 2023. Our findings reveal that the funds which outperform the other funds invest predominantly in domestic stocks. In contrary to this, poor performing funds mainly hold foreign stocks or foreign ETFs in their portfolio compositions. Sensitivity analysis results state the high degree of stability related to proposed approach via the weights of criteria obtained. Besides, according to the comparison analysis, proposed IVCIF AHP – ERUNS method is valid and applicable. Following that, we provide managerial and practical implications along with the future suggestions.